2019
DOI: 10.1016/j.molimm.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory network behind MHC class I expression

Abstract: The MHC class I pathway, presenting endogenously derived peptides to T lymphocytes, is hijacked in many pathological conditions. This affects MHC class I levels and peptide presentation at the cell surface leading to immune escape of cancer cells or microbes. It is therefore important to identify the molecular mechanisms behind MHC class I expression, processing and antigen presentation. The identification of NLRC5 as regulator of MHC class I transcription was a huge step forward in understanding the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 87 publications
2
113
0
Order By: Relevance
“…Previous studies showed that EZH2 mutations may mediate MHC-II expression through downregulation of CIITA, which is the master regulator of MHC-II genes (35). In addition, NLRC5 has been recently identified as a transactivator of MHC class I, which was shown to regulate MHC-I expression by reducing H3K27me3 on the MHC-I promoter (10,36). As shown in several previous publications, the expression levels of NLRC5 and MHC-I are highly correlated, with more NLRC5 resulting in higher MHC-I expression and increased MHC-I cell surface levels (10,37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that EZH2 mutations may mediate MHC-II expression through downregulation of CIITA, which is the master regulator of MHC-II genes (35). In addition, NLRC5 has been recently identified as a transactivator of MHC class I, which was shown to regulate MHC-I expression by reducing H3K27me3 on the MHC-I promoter (10,36). As shown in several previous publications, the expression levels of NLRC5 and MHC-I are highly correlated, with more NLRC5 resulting in higher MHC-I expression and increased MHC-I cell surface levels (10,37).…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP-responsive element binding protein 1 (CREB1) and the activating transcription factor 1 (ATF1) bind the X2 box; the nuclear transcription factor Y (NFY) complex interacts with the Y box. Instead, the elements interacting with W/S box remains poorly defined [ 106 , 107 ]. The interactors with SXY module of genes belonging to both HLA class I and II are crucial elements in the transcriptional control.…”
Section: Human Leucocyte Antigen and Antigen Presentation Machinermentioning
confidence: 99%
“…The administration of IFNs might effectively counteract HLA class I down-regulation in cancer cells by boosting the presentation of tumor specific-associated antigens [ 254 , 255 , 256 , 257 ]. A phase 0 clinical trial showed that systemic administration of IFN-γ increases not only HLA class I expression on tumor cells, but also T-cell infiltration in cold tumors [ 258 ] IFN-mediated up-regulation of HLA class I derived peptide complexes occurs via activation of the Jak/STAT pathway which induces the binding of IRFs to ISRE motifs located in HLA class I promoter region [ 107 , 254 ]. In addition, IFN-γ-mediated HLA class I derived peptide complex up-regulation is also associated to an increased histone demethylation and acetylation of APM genes in the MHC locus, particularly of histone H3 in TAP1 promoter locus [ 259 ].…”
Section: Restoring Hla Class I Expression As a Novel Therapeutic Smentioning
confidence: 99%
“…Nevertheless, reduction of MHC-I expression is a reversible state. Type I and type II interferon signaling contribute to the upregulation of MHC-I on tumor cells [28,[48][49][50]. In our previous studies [9] we showed that replicating arenaviruses induce a strong interferon response via the activation of the innate immune response.…”
Section: Furthermore Replicating Non-oncolytic Arenaviruses Like Lcmmentioning
confidence: 96%